Potential Effects of Liraglutide on Male Reproductive Dysfunction Associated with Obesity - Mohamed Abdel Raouf ElGhannam, Reham Hassan Ibrahim, Nada Abdel Maksoud Mohamed Salah Eldeen, Lamiaa Goda Mohammad (Cuestiones de Fisioterapia, 2024)
Background: Obesity is increasingly recognized as an important contributor to male reproductive dysfunction through hormonal imbalance, insulin resistance, chronic inflammation, oxidative stress, impaired hypothalamic-pituitary-gonadal axis activity, and direct damage to testicular tissue. These alterations may reduce testosterone production, impair spermatogenesis, decrease sperm quality, and increase the risk of hypogonadism and infertility. Liraglutide, a glucagon-like peptide-1 receptor agonist, is widely used for glycemic control and weight management and may exert additional reproductive benefits through metabolic, anti-inflammatory, antioxidant, and endocrinemechanisms. This review evaluates the potential effects of liraglutide on obesity-associated male reproductive dysfunction